The prevalence and management of diabetes mellitus complications at Mankweng Hospital, Limpopo Province - Nyamazana, Tawanda (My University, 2019)
Diabetes mellitus (DM) is a major public health problem, challenging patients, healthcare professionals, health planners and policy makers worldwide. Its prevalence has been on the rise for the past four decades, with this trend expected to continue. With this challenge, the management of DM should be done following evidence-based guidelines to prevent or slow down the development of DM-related complications. According to the Society of Endocrinology Metabolism and Diabetes South Africa (SEMDSA) guidelines, it has been shown that strict glycaemic control and proper clinical monitoring can help with prevention and slowing down development of complications. If left untreated or poorly controlled, DM progresses into an array of complications which may increase morbidity and mortality. The prevalence and management of DM complications was investigated. Objectives: • To determine the prevalence of DM complications at Mankweng Hospital. • To evaluate the management of patients with DM complications at Mankweng Hospital. • To determine the factors contributing to the development of complications. • To determine preventive measures taken on non-complicated patients to prevent them from complicating. Method: A retrospective longitudinal review of 134 randomly selected patient records was conducted for a five-year period spanning from June 2012 to May 2017. A pretested DM complications checklist was used to collect data from the patient records. A cross-sectional study was conducted amongst healthcare professionals caring for patients with DM. A total of 41 healthcare professionals were included in the study where a self-administered questionnaire was used to obtain the data. Both sets of data obtained were analysed using IBM SPSS version 25. xiii Results: Retrospective study The study sample population was entirely consisted of African patients with 70.1% (n=94) females and 29.9% (n=44) males. In the sample, 17.2% were suffering from T1DM while 82.8% were suffering from T2DM. The complications with the highest prevalence were diabetic nephropathy, peripheral neuropathy and diabetic retinopathy with prevalence of 35.8%, 32.1% and 22.4% respectively. Vascular diseases, autonomic neuropathy and diabetic foot ulcer had prevalence of 9.7%, 9% and 6% respectively. The overall prevalence of complications in general was 67.2% which was very high. Cross-sectional study A self-administered questionnaire was distributed amongst 41 healthcare professionals (14 males and 27 females). This sample consisted of 9.8% doctors, 41.5% pharmacists, 17.1% professional nurses, 17.1% physiotherapists, 2.4% podiatrists and 12.2% optometrists. It was discovered that only 92.6% and 84.6% of the participants were compliant with the guidelines in terms of random blood glucose tests and blood pressure (BP) per every visit. Only 50% of the HCPs revealed that HbA1c tests should be done according to the guidelines. Merely 5.6%, 8.3%, 5.3% and 22.7% of the HCPs correctly indicated the frequency of foot examinations, eye examinations, renal function tests and lipogram tests respectively, as per the guidelines. Patient related factors were rated as the most contributory factors (56.4%) to the development of complications. Socio-economic and medication related factors had most of the HCPs (36.1% and 29% respectively) rating them as moderate in terms of how much they contribute to the development of complications. The factors rated the least were healthcare team (32.4%) and health system (33.3%) related factors. Conclusion: There was a high prevalence of overall complications in general, with diabetic nephropathy, peripheral neuropathy and diabetic retinopathy being the three highest individual complications. There was poor monitoring of patients with complications as the compliance with the SEMDSA guidelines was very low. Patient related factors xiv were rated the most contributory factors to the development of complications in patients with DM. Recommendations: There is need to implement patient-centred DM care which makes sure that the patient is involved in decision making so that they take responsibility of their own health. There is need for the development and implementation of institutional quality improvement programs where regular audits of the processes of DM care and outcomes are monitored. Limitations: • The limitations of the study are that the researcher completely relied on patient records. • The sample size for HCPs was very small and therefore the study results cannot be generalised.
Thesis (M. Pharm) -- University of Limpopo, 2019
Keywords: Diabetes mellitus; Diabetes mellitus complications; Diabetes -- South Africa -- Limpopo; Diabetes -- Complications; Diabetics -- South Africa -- Limpopo; Diabetes -- Treatment -- South Africa -- Limpopo